Biochemistry / Mary K. Campbell ; illustration concepting and illustrations: J/B Woolsey Associates. - Campbell, Mary K. (Saunders golden sunburst series, 1999)
This text is intended for students in any field of science or engineering who want a one-semester introduction to biochemistry, but who do not intend to major in biochemistry